STUDI PENILAIAN KEANDALAN BANGUNAN GEDUNG - Nicholas Taurino; Henny Wiyanto (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2022)
Building reliability is the ability of a building to carry out its functions according to plan. But in reality there are cases where buildings are not reliable. Therefore it is necessary to assess the reliability of the building in order to know the value of the reliability of a building so that it can be concluded whether the building is still functional or not. So a study was conducted on the assessment of the reliability of buildings that cover 5 aspects of the building, namely aspects of architecture, structure, utilities, accessibility, and building and environmental layout. The assessment will be carried out according to the existing function weights for the five aspects of the assessment. Evaluation is broadly carried out using visual observation methods and specifically for the aspect of utility the document study method is used as an additional. Can be known reliability in each aspect with the existing reliability classification. After evaluating each aspect, a comprehensive reliability assessment will be carried out with the weight of existing functions and can be known whether the building is reliable, less reliable, or unreliable through the existing reliability classifications and it can be seen whether the building is still in a worthy condition or not.